2002
DOI: 10.1093/annonc/mdf154
|View full text |Cite
|
Sign up to set email alerts
|

A three-arm phase III randomised trial comparing combinations of platinum derivatives, ifosfamide and/or gemcitabine in stage IV non-small-cell lung cancer

Abstract: In stage IV NSCLC, treatment with regimens including the new drug gemcitabine were associated with a better but not statistically significant observed survival compared with a classical first-generation cisplatin-containing regimen. The non-platinum combination of gemcitabine was as effective as its combination with platinum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Other trials showed similar response rates and survival, and less toxicity in patients treated with nonplatinum-based schedules compared to platinum-containing combinations (Gatzemeier et al, 1991;Gridelli et al, 1996;Georgoulias et al, 2001;Sculier et al, 2002). A recently published study compared four platinum-based regimens for advanced NSCLC (cisplatin with either paclitaxel, gemcitabine, or docetaxel, and carboplatin with paclitaxel), and showed no difference in survival (the median survival was 7.9 months for all patients) and response rate (19% for all patients).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other trials showed similar response rates and survival, and less toxicity in patients treated with nonplatinum-based schedules compared to platinum-containing combinations (Gatzemeier et al, 1991;Gridelli et al, 1996;Georgoulias et al, 2001;Sculier et al, 2002). A recently published study compared four platinum-based regimens for advanced NSCLC (cisplatin with either paclitaxel, gemcitabine, or docetaxel, and carboplatin with paclitaxel), and showed no difference in survival (the median survival was 7.9 months for all patients) and response rate (19% for all patients).…”
Section: Discussionmentioning
confidence: 95%
“…Phase III studies have reported similar response rates and overall survival in cisplatin and noncisplatin-based regimens. However, in the majority of these trials the nonplatinum regimens had a more favourable toxicity profile (Gatzemeier et al, 1991;Gridelli et al, 1996;Georgoulias et al, 2001;Kosmidis et al, 2002;Sculier et al, 2002).…”
mentioning
confidence: 99%
“…Responses were assessed according to the usual criteria (Sculier et al, 2002b). Complete remission was defined as the disappearance of all signs of disease, for at least 4 weeks.…”
Section: Criteria Of Evaluationmentioning
confidence: 99%
“…Although poor PS was always considered a poor prognostic factor for survival, it was an independent poor prognostic factor for response in two trials [10,11], while it was not in others [12][13][14]. In the present study, the recently completed randomised trial in advanced NSCLC (European Lung Cancer Working Party (ELCWP) protocol 01995) [15,16] was retrospectively analysed in order to determine if cisplatin-based chemotherapy was associated with clinical improvement in patients with poor PS (Karnofsky 60-70).…”
mentioning
confidence: 99%